ENGLISH LEARNING STRATEGIES USED IN THE PESANTREN NURUL IMAN AL HASANAH TO INCREASE STUDENTS SPEAKING SKILL - Muhamad Khoerul Hadist; Muhamad Faisal Anwar (JELLi Journal, 2023)
The objectives of the research are to find out what is the English learning strategies used in the Pesantren Nurul Iman Al Hasanah to increase students speaking skill, and to what extent does the strategies help the students to increase students speaking skill in Pesantren. The writer conducted this research in terms of strategies of English that used in the Pesantren. In this research, the writer used descriptive qualitative method, and purposive sampling. This study used observation and interview for data collecting technique and was conducted from June 1th, 2022 until June 29th, 2023. The result shows the strategies that used in the Pesantren Nurul Iman Al Hasanah helps the students to increase their speaking skill. All the strategies that used in the Pesantren can helping them to increasing student’s speaking skill. The strategies that used in the Pesantren make the teacher easier to achieve learning goals.